Prevalence, incidence, and risk factors of primary open-angle glaucoma - a cohort study based on longitudinal data from a German public health insurance - D. Kreft; G. Doblhammer; R. F. Guthoff; S. Frech (BMC, 2019)
Abstract Background This study estimates the prevalence and incidence rates of primary open -angle glaucoma (POAG) as well as risk factors based on a dataset from the largest German health insurance company. Methods A random sample of 250,000 persons at age 50+ of the Allgemeine Ortskrankenkasse (AOK) from 2010 to 2013 was used. Selected risk factors of POAG incidence were analyzed using multivariate Cox proportional hazard models. Results The age-standardized prevalence of POAG at age 50+ in 2010 was 2.79% (95%-CI: 2.72-2.85%). The age-standardized total incidence rate was 0.38 (0.36-0.39) per 100 person-years. Sex differences were significant for total prevalence and total incidence rates, with higher prevalence and incidence rates for women compared to men. The Cox model revealed a strong age effect, a significantly 19% higher incidence for women (p ≤ 0.001), injuries of the eye and orbit (175%, p ≤ 0.001), degeneration of iris and ciliary body (155%, p = 0.022), myopia (155%, p ≤ 0.001), retinal vascular occlusions (134%, p ≤ 0.001), hypertension (13%, p ≤ 0.001) and diabetes mellitus (23%, p ≤ 0.001). Conclusion Health claims data are an important data source for estimating POAG occurrence and help overcome the problems of small sample sizes. These results may help to understand the causal pathways of POAG and to develop intervention strategies to increase the awareness of patients and physicians with the aim of reducing POAG incidence.